2014
DOI: 10.5606/tgkdc.dergisi.2014.9397
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of bronchial carcinoid tumors: 11-year experience

Abstract: Bu çalışmada, bronşiyal karsinoid tümörlü hastalarda cerrahi tedavi, ameliyat sonrası komplikasyonlar ve uzun dönem sonuçlar sunuldu. Ça lış mapla nı:Ocak 2000-Aralık 2010 tarihleri arasında ameliyat öncesi ve sonrası patolojik olarak bronşiyal karsinoid tümör olduğu doğrulanmış 57 hastaya (34 kadın, 23 erkek; ort. yaş 43 yıl; dağılım 13-83 yıl) akciğer rezeksiyonu uygulandı. Cerrahi tipi, karsinoid tümörün histopatolojik tipi, ameliyat sonrası komplikasyonlar ve uzun dönem sonuçlar değerlendirildi. Bul gu lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The latest publications also noted that parenchyma-sparing resections are suitable for proximal carcinoid tumors. [12] In conclusion, we demonstrated that atypical presentation (p= 0.005), and nodal invasion (p= 0.008) were both negative prognostic factors. Prognosis does not seem to be related to sex (p= 0.433), age (p= 0.474), smoking history (p= 0.726), comorbidity (p= 0.062), central or peripheral localization (p= 0.717), or T status (p= 0.300).…”
Section: Discussionmentioning
confidence: 57%
“…The latest publications also noted that parenchyma-sparing resections are suitable for proximal carcinoid tumors. [12] In conclusion, we demonstrated that atypical presentation (p= 0.005), and nodal invasion (p= 0.008) were both negative prognostic factors. Prognosis does not seem to be related to sex (p= 0.433), age (p= 0.474), smoking history (p= 0.726), comorbidity (p= 0.062), central or peripheral localization (p= 0.717), or T status (p= 0.300).…”
Section: Discussionmentioning
confidence: 57%